Sustainable Elegance: The Role of Green Aesthetics in the Fashion Industry - Giulia Maieli (ZoneModa Journal, 2025)
In an era of unprecedented technological change and fast-paced consumerism, we are witnessing a renewed appreciation for nature’s beauty, influencing aesthetic paradigms. Although Kantian and Burkean notions of the sublime historically framed nature as separate from human experience, contemporary challenges have led to a different consideration of this relationship. Movements like Art Nouveau and Arts and Crafts pioneered organic designs in objects, clothes, wallpapers, and upholstery of every kind. Today, climate crisis and the environmental impact of the fashion industry — which ranks as the world’s seventh most polluting industry — demand designers to find sustainable solutions, such as the use of innovative biomaterials and natural dyes (derived from plants, insects or minerals), reducing pollution and waste. A green aesthetic represents more than a simple choice of style: it embodies a call for a more responsible future, where beauty is about living in harmony with the environment we live in. This study explores the significant impact that a green(er) aesthetics has on the fashion industry, thus reflecting a broader movement towards sustainability that encompasses sustainable innovations in designs, materials, and communication.